New 2,4-bis[(substituted-aminomethyl)phenyl]phenylquinazoline and 2,4-bis[(substituted-aminomethyl)phenyl]phenylquinoline Derivatives: Synthesis and Biological Evaluation as Novel Anticancer Agents by Targeting G-Quadruplex - Jean Guillon; Marc Le Borgne; Vittoria Milano; Aurore Guédin-Beaurepaire; Stéphane Moreau; Noël Pinaud; Luisa Ronga; Solène Savrimoutou; Sandra Albenque-Rubio; Mathieu Marchivie; Haouraa Kalout; Charley Walker; et al. (Pharmaceuticals, 2023)
The syntheses of novel 2,4-bis[(substituted-aminomethyl)phenyl]phenylquinazolines 12 and 2,4-bis[(substituted-aminomethyl)phenyl]phenylquinolines 13 are reported here in six steps starting from various halogeno-quinazoline-2,4-(1H,3H)-diones or substituted anilines. The antiproliferative activities of the products were determined in vitro against a panel of breast (MCF-7 and MDA-MB-231), human adherent cervical (HeLa and SiHa), and ovarian (A2780) cell lines. Disubstituted 6- and 7-phenyl-bis(3-dimethylaminopropyl)aminomethylphenyl-quinazolines 12b, 12f, and 12i displayed the most interesting antiproliferative activities against six human cancer cell lines. In the series of quinoline derivatives, 6-phenyl-bis(3-dimethylaminopropyl)aminomethylphenylquinoline 13a proved to be the most active. G-quadruplexes (G4) stacked non-canonical nucleic acid structures found in specific G-rich DNA, or RNA sequences in the human genome are considered as potential targets for the development of anticancer agents. Then, as small aza-organic heterocyclic derivatives are well known to target and stabilize G4 structures, their ability to bind G4 structures have been determined through FRET melting, circular dichroism, and native mass spectrometry assays. Finally, telomerase inhibition ability has been also assessed using the MCF-7 cell line.